On gas source declaration methods for single-robot search - Ojeda, Pepe; González-Monroy, Javier; González-Jiménez, Antonio Javier (My University, 2022)
Source declaration, along with plume finding and plume tracking, is one of the needed processes for gas source localization (GSL). It is a fundamental part of the search, since it is responsible to decide whether the gas source has been found, and also to pinpoint its location. Despite its importance, source declaration is often ignored in most of the GSL research, the criteria for termination being selected in a seemingly arbitrary manner, or even not being discussed at all. A clear example of this is the large number of experiments in the literature that are declared concluded whenever the robot manages to physically reach the source, without formally declaring it. In this work, we seek to provide an overview of the most significant declaration methods that have been used in state-of-the-art research for single-robot GSL, analyzing their strengths and weaknesses. We also provide a preliminary experimental validation of these methods, focusing on how stable their performance is when their input parameters are modified.
Keywords: Gas source localization; GSL; Single-robot; Machine olfaction; Gas source declaration; Gas-Industria-Automatización; Robots industriales; Fuentes de energía-Robótica; Robotic Olfaction; Source Declaration; Source Localization